Reclassifying hypertension phenotypes in adolescents by ambulatory blood pressure monitoring: implications of the 2022 AHA guidelines in a Brazilian birth cohort. - Machado, Ivan Coelho; Facincani, Inalda; Lino, Mariana Cachero; Pap, Gabriela; Coelho, Eduardo Barbosa; Cardoso, Viviane Cunha; Carmona, Fabio (Pediatric Nephrology, 2025)
Background: Hypertension in adolescents is a growing public health concern, with ambulatory blood pressure monitoring (ABPM) playing a key role in diagnosis. The 2022 American Heart Association (AHA) guidelines introduced substantial changes to ABPM classification criteria, with the exclusion of the blood pressure (BP) load criterion and the alignment of diagnostic thresholds with adult values. This study aimed to assess the impact of guideline revisions on the prevalence of hypertension phenotypes among Brazilian adolescents. Methods: We conducted a cross-sectional study of 1006 adolescents (aged 11–13 years) from the BRISA cohort in Ribeirão Preto, Brazil. Participants underwent 24-h ABPM and clinic BP (cBP) assessment. Hypertension phenotypes were classified according to both the 2014 and 2022 AHA guidelines. Statistical analysis included prevalence comparisons, reclassification patterns, and centroid-based phenotypic analysis. Results: The prevalence of cBP hypertension was 3.4%. Using either the 2014 or 2022 AHA criteria, around 13% of adolescents were classified as hypertensive. However, under the 2014 guidelines, nearly 20% of the cohort remained unclassified, primarily due to elevated BP load alone. These individuals were reclassified as normotensive under the 2022 criteria, leading to a 20% increase in this group. One in ten adolescents was diagnosed with masked hypertension. Among hypertensive individuals, half had elevated nighttime BP only. Conclusions: The 2022 AHA guideline revisions improved the clarity of hypertension classification in this prenatal cohort. These findings support the clinical utility of the updated criteria and highlight the importance of adapting ABPM interpretation to current standards.